A review of the literature: determinants of online learning among students - Tang, Hasnah King Yee; Wong, Su Luan; Mohd Ayub, Ahmad Fauzi; Mahmud, Rosnaini (Eurojournals, 2009)
The use of Information Technology and the Internet as a teaching and learning tool is rapidly expanding into today’s learning environments (Liaw, Huang, & Chen, 2007). Specifically, the Internet has been used as a medium to conduct online learning and this has made learning more complex in such a learning environment (Sun et al., 2008). Sun et al. (2008) forewarned that such complex learning environments can cause online learners to drop out. For this reason, the main purpose of this review paper is to explore the factors that can influence the use of online learning among students. Based on a review of the literature, this paper suggests that there are four main determinants of online learning which are gender, attitudes toward online learning, perceived ease of use and perceived usefulness.